Improvement of blended cement characteristics as possible alternative for oil well cement - Samsuri, Ariffin; Subbiah, Surej Kumar (1997)
The paper presents the results of the laboratory studies on locally produced blended cement as an oil well cement. The results show that the blended cement has less free water, less fluid loss, better strength development but shorter thickening time than G cement. In addition, the results also show that there is a great increase in strength development by adding the palm oil fly ash. However, there will be a decrease in strength if more than 15% of the fly ash is added to the cement. The cost per bag of blended cement is cheaper and there will be a saying of about 48% of the cement material cost if the blended cement is used to cement an average oil well at 8000ft depth. In general, the blended cement showed a better results than G cement as the water cement ratio been varied even though as the ratio increases the free water and fluid loss also increases. Blended cement proves to be the alternative choice for the replacement of G cement in cementing job, particularly for the shallow well due to the shorter thickening time.